The manifestation and causes of public panic in the early stage of COVID-19 in China: a framework based on consciousness-attitude-behavior - Wei, Changwei; Xu, Jiaxi; Xu, Zuying (Frontiers in Public Health, 2024)
BackgroundThe onset of the COVID-19 pandemic brought about a stark and devastating impact on global scales, affecting countries and their citizens profoundly. The public’s lack of readiness for such an enigmatic and virulent threat led to widespread alarm, catalyzing a paradigm shift in both public conduct and governmental tactics. In the midst of this urgency, there was a notable lack of studies on the initial panic waves. Our study is designed to investigate the dynamics of public panic during the early stages of the pandemic, including its origins, and the public’s perceptions and behaviors.MethodsOur research, conducted through a questionnaire survey employing snowball sampling, gathered critical data on the public’s awareness, attitudes, and behaviors related to panic between February 23rd and March 25th, 2020.ResultsThe findings indicate a period of exceptionally intense and authentic public panic. This panic was a pervasive sentiment, manifesting in strong endorsements for rigorous epidemic control measures and heightened anxiety over virus-related information and family safety. The rapid spread of panic was also a notable characteristic.ConclusionThe public panic in response to COVID-19 was modulated by stringent prevention measures, with anxiety levels differing significantly based on occupation and health awareness. Notably, the rise of suspicious and distrustful actions was inextricably linked to an overwhelming sense of fear that gripped the public.